Enterprise Strategy to Sustain Continuous Innovation and Product Quality Consistency in a Saturated Market - Eddine, Belouadah Ahmed Seif; Fared, M. Abid (Bulletin of Science, Technology and Society, 2024)
A highly competitive and saturated market creates a major challenge for enterprises to maintain continuous innovation and consistency in product quality. Innovation is the key to creating relevant and attractive products, but it often faces the dilemma of the need to maintain high quality. In addition, limited resources for research and development (R&D), as well as intense competition, mean that enterprises must be careful to allocate their limited funds and resources to create innovations that are not only new but also of high quality. Other challenges include efficient supply chain management, managing the risks associated with new product launches, and the difficulty of adapting to rapid changes in consumer preferences. In these conditions, a culture of innovation that supports experimentation and the courage to take risks, as well as effective communication between departments, is an important factor in maintaining quality consistency and innovation. Enterprises that are able to maintain a balance between quality and innovation, while continuing to adapt to market needs, will be better able to survive and thrive in saturated markets. This research provides important insights for enterprises to overcome existing challenges and formulate effective strategies to maintain competitiveness in competitive markets.